The Effect of School Principals' Academic Supervision and Teachers' Professional Competence on The Quality of Learning in Elementary Schools - Listiyanto, Hery; Kusumaningsih, Widya; Sulianto, Joko (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of principals' academic supervision and teachers' professional competence on the quality of learning in elementary schools. Using a quantitative approach and a survey of 138 teachers, data were collected via a Likert-scale questionnaire and analyzed using simple and multiple linear regression in SPSS version 29. The results showed that principals' academic supervision had a positive and significant effect on the quality of learning (r = 0.520; contribution 27%). Teachers' professional competence also had a positive and significant effect, with a correlation coefficient (r = 0.733) and a coefficient of determination (R² = 0.538), accounting for 53.8% of the variation in learning quality (p < 0.001). Together, academic supervision and teachers' professional competence explained 70% of the variation in learning quality (R² = 0.700; Adjusted R² = 0.695). This regression model was significant (F = 32.879; p < 0.001), indicating that both independent variables explained 70% of the variance in learning quality. These findings suggest that improving academic supervision and strengthening teachers' professional competencies can improve the quality of learning in elementary schools.